The Role of Verbs in Sentence Production - Antón-Méndez, Inés (Frontiers in Psychology, 2020)
To investigate the role of verbs in sentence production, the experiment reported here employed a simple sentence elicitation technique based on separate elicitor images for the different sentence constituents: subject, verb, and verbal modifier. This permitted presenting them in different temporal configurations to see whether the time taken to start uttering the subject of a sentence was contingent on having access to information about the action that would determine verb selection. The results show that sentence onset latencies varied in relation to the presentation of the verb elicitor, suggesting sentence processing depends crucially on having access to the information pertaining to the verb. What is more, increases in the lexical frequency of the actual verbs used significantly reduced onset latencies for the subject noun as expected if the verb lemmas have to be retrieved before the sentence can be processed. Among other things, this argues against strict linearity and in favour of hierarchical incrementality in sentence production. Additionally, the results hint at the possibility that other obligatory sentence constituents (namely, direct objects in transitive sentences) may also have to be available before the sentence can be processed.